Virtualization for security : including sandboxing, disaster recovery, high availability, forensic analysis, and honeypotting - Hoopes, John (Syngress Pub., 2009)
One of the biggest buzzwords in the IT industry for the past few years, virtualization has matured into a practical requirement for many best-practice business scenarios, becoming an invaluable tool for security professionals at companies of every size. In addition to saving time and other resources, virtualization affords unprecedented means for intrusion and malware detection, prevention, recovery, and analysis. Taking a practical approach in a growing market underserved by books, this hands-on title is the first to combine in one place the most important and sought-after uses of virtualization for enhanced security, including sandboxing, disaster recovery and high availability, forensic analysis, and honeypotting.